Design and analysis effectiveness photobook as chinese-hokkian marriage medium information culture to batam city Gen-Z - Winsley; Deli (LPPMPK - Sekolah Tinggi Teknologi Muhammadiyah Cileungsi, 2024)
Indonesia's cultural diversity faces challenges from modernization, which has an impact on traditional Chinese wedding customs in Batam City. To address this, a photobook project has been initiated to document and preserve Chinese-Hokkien wedding traditions. This study focuses on providing a detailed description of the content of photobooks and to assess the effectiveness of using photobooks as a medium of information about Chinese-Hokkien wedding traditions in Batam City. The target population for this study is the Chinese Gen Z community in Batam. The sample size was determined using the Slovin sampling formula, which resulted in 400 respondents. The 4D application model was used to guide the project through the stages of definition, design, development and deployment, incorporating methods such as the Guttman Scale for quantitative analysis used to calculate the effectiveness of using photobooks as an information medium. To collect quantitative data, a closed question model questionnaire was used, consisting of 10 questions related to the content of the photobook, including the type of font used, color theme, layout, and understanding of the book's message. Results from further testing validated the project's success with a positive acceptance rate of 81.6%. This photobook project serves as a valuable tool to educate and engage audiences about the historical and cultural significance of Chinese-Hokkien wedding rituals, contributing to the preservation of Indonesia's rich cultural heritage. Based on the analysis of the questionnaire results and feedback from respondents, it can be concluded that the photobook is effective as a promotional and information medium for Chinese-Hokkien wedding traditions in Batam City